The enlightenment of Chinese philosophy to the construction of contemporary ecological civilization - Zhang, Ziyu (2024)
Chinese philosophy is a philosophy of ecology. The basic problem of Chinese philosophy is the relationship between heaven and man, that is, the relationship between nature and man. This is evident in the main schools of Chinese philosophy, such as Confucianism and Taoism. A correct understanding and evaluation of Chinese ecological philosophy has important practical significance for us to reflect on the ecological imbalance and environmental deterioration caused by the industrial civilization, created under the guidance of the mechanical concept of nature and anthropocentrism, and to re-examine the way of human existence, development, thinking and values. This paper aims to explore the elements of eco-philosophy in Chinese philosophy and analyze its influence on the concept, value and practice of ecological civilization.